ANALISIS KEBUTUHAN DALAM PERANCANGAN SISTEM INFORMASI TATA KELOLA KEUANGAN BENGKEL - Monica, Shella; Wira Trise Putra, Dede; Yoga Swara, Ganda; Warman, Indra; Anisya (Universitas Lampung, 2025)
Sunrise Jaya Motor Workshop experiences difficulties in transaction recording, inventory management, and mechanic bonus distribution, which affects the preparation of financial reports. This study employs the Waterfall method, focusing on two main stages: recruitment for collecting user requirements and design for system development. The recruitment stage involves identifying the workshop's operational needs through interviews, observations, and document studies, while the design stage produces a data model in the form of an Entity Relationship Diagram (ERD), a business process flow using Business Process Model and Notation (BPMN), and a user interface design in the form of wireframes. The results of this requirements analysis are expected to serve as the foundation for developing a workshop information system that can improve operational efficiency, simplify transaction recording, and facilitate financial reporting.